2009
DOI: 10.1242/jcs.027508
|View full text |Cite
|
Sign up to set email alerts
|

Mild mitochondrial uncoupling induces 3T3-L1 adipocyte de-differentiation by a PPARγ-independent mechanism, whereas TNFα-induced de-differentiation is PPARγ dependent

Abstract: Impairment of mitochondrial activity affects lipid-metabolizing tissues and mild mitochondrial uncoupling has been proposed as a possible strategy to fight obesity and associated diseases. In this report, we characterized the 3T3-L1-adipocyte `de-differentiation' induced by carbonyl cyanide (p-trifluoromethoxy)-phenylhydrazone (FCCP), a mitochondrial uncoupler. We found a decrease in triglyceride (TG) content in adipocytes incubated with this molecule. We next analyzed the expression of genes encoding adipogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 76 publications
11
53
0
Order By: Relevance
“…We investigated in vivo whether changes in the expression of genes involved in metabolism were at least partially mediated by cellautonomous effects in adipocytes. Consistent with the action of positive uncouplers described in a previous report [43], CZ5 enhanced Pgc-1α expression and reduced Leptin expression in adipocytes via incubation during differentiation (ESM Fig. 6).…”
Section: Discussionsupporting
confidence: 90%
“…We investigated in vivo whether changes in the expression of genes involved in metabolism were at least partially mediated by cellautonomous effects in adipocytes. Consistent with the action of positive uncouplers described in a previous report [43], CZ5 enhanced Pgc-1α expression and reduced Leptin expression in adipocytes via incubation during differentiation (ESM Fig. 6).…”
Section: Discussionsupporting
confidence: 90%
“…In mature adipocytes, fat accumulation can be regulated by modulation of mitochondrial respiration in vitro and in vivo. Mild mitochondrial uncoupling by FCCP in 3T3-L1 cells decreases triglyceride content, without affecting PPARγ and C/EBPα expression (35). In mice, low doses of the mitochondrial uncoupling agent 2,4-dinitrophenol enhances tissue respiratory rates and decreases body weight (36), and ectopic expression of the uncoupling protein 1 (UCP1) in WAT protects Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While brown adipose tissue ( BAT) converts mitochondrial energy into heat during adaptative thermogenesis, characterization of WAT mitochondria function is still incipient (Forner et al, 2009;De Pauw et al, 2009). A recent in vivo proteomics analysis in mice WAT and BAT shows that there are quantitative and qualitative differences between the mitochondria from both tissues: BAT mitochondria are more similar to muscle mitochondria and WAT mitochondria express proteins associated with anabolic functions and proteins involved in the degradation of xenobiotics (Forner et al, 2009).…”
Section: Wat Mitochondria In Obesity and Inflammationmentioning
confidence: 99%
“…A recent in vivo proteomics analysis in mice WAT and BAT shows that there are quantitative and qualitative differences between the mitochondria from both tissues: BAT mitochondria are more similar to muscle mitochondria and WAT mitochondria express proteins associated with anabolic functions and proteins involved in the degradation of xenobiotics (Forner et al, 2009). Recent studies suggest that mitochondrial biogenesis and metabolism are implicated in the regulation of various processes in WAT, such as pre-adipocytes proliferation, adipogenesis, carbohydrate and lipid metabolism, adipocyte de-differentiation, TAG accumulation and acquirement of BATlike characteristics (De Pauw et al, 2009;Forner et al, 2009;Tedesco et al, 2010;Bordicchia et al, 2012;Koponen et al, 2012) and impaired mitochondrial biogenesis contributes to the onset of obesity and related metabolic disorders, such as insulin resistance (Tedesco et al, 2010).WAT mitochondrial biogenesis in mice is correlated with the up-regulation of genes involved in fatty acid oxidation and mitochondrial electron transport activity, boosting WAT catabolism (Granneman et al, 2005). Indeed, it was demonstrated that mitochondrial proliferation and remodeling are enhanced in 3T3-L1 cells during adipogenesis and the use of insulin sensitizers, such as rosiglitazone, leads to significant alterations in mitochondrial morphology and augmentation of the expression of several mitochondrial proteins (Wilson-Fritch et al, 2003).…”
Section: Wat Mitochondria In Obesity and Inflammationmentioning
confidence: 99%